(untitled) (Ozone Therapy Global Journal, 2014)
The root canal treatment has been dramatically changed since the emergence of ozone therapy.Due toits potent antimicrobial activity and biocompatibility, ozone can be applied as an agent to improve decontamination procedures and possibly increase success rates. The aim of this study was to compare the antimicrobial activity of 3different concentrations of aqueous ozone on Pseudomonas aeruginosa, Staphylococcus aureus, and Enterococcus faecalis.This study used a standardized suspension of 3 bacteria. These suspensions were cultivated and spectrophotometrically adjusted to a final concentration of 4.46X108 CFU/mL.Then they were submitted to groups: Group I – aqueous ozone 2 μg/mL; Group II – aqueous ozone 5 μg/mL; Group III – aqueous ozone 8 μg/mL, and Group Control – bidistilled cold sterile water with no ozone. Bidistilled cold sterile water was ozonated for 5 minutes. Then 10 mL of each suspension were added to 90 mL of each group in a glass flask. After 1 minute of contact, 1 mL of each flask was added to 9 mL of 0.1% sodium tiossulfate to neutralize the ozone, and then serial dilution was performed. After 24 hours of incubation, the CFU counting was performed. In parallel, 1 mL of each glass flask was added to 9 mL of TSB broth and incubated for 7 days for visual analyses of turbidity broth. The results showed Group I presented Enterococcus faecalis growth. Group II and III presented no CFU counting, but aqueous ozone at 5 μg/mL presented 2 bleary tubes of Enterococcus faecalis, indicating bacterium growth. Group III (aqueous ozone 8 μg/mL) showed no CFU counting or blurry broth. According to the applied methodology, it was possible to conclude that the aqueous ozone in concentration of 8 μg/mL was the most efficient to eliminate the three evaluated bacteria.